Organizational Conflict: Concepts and Models - Pondy, Louis R. (Administrative Science Quarterly, 1967)
Three types of conflict among the subunits of formal organizations are identified: (1) bargaining conflict among the parties to an interestgroup relationship; (2) bureaucratic conflict between the parties to a superior-subordinate relationship; and (3) systems conflict among parties to a lateral or working relationship. In each of the three cases, conflict is treated as a series of episodes, each episode including stages of latency, feeling, perception, manifestation, and aftermath. The organization's reaction to conflict in each case is analyzed using the Barnard-Simon model of inducements-contributions balance theory. Of particular interest is whether the organization members resolve conflicts by withdrawing from the organization, by altering the existing set of relationships, or by changing their values and behavior within the context of the existing relationships.1 Louis R. Pondy is assistant professor of business administration at the University of Pittsburgh.